2018
DOI: 10.1111/php.12877
|View full text |Cite
|
Sign up to set email alerts
|

Photobiomodulation in the Metabolism of Lipopolysaccharides‐exposed Epithelial Cells and Gingival Fibroblasts

Abstract: This study assessed the effects of photobiomodulation (PBM) to cells previously exposed to lipopolysaccharides (LPS). Human gingival fibroblasts (HGF) and epithelial cells (HaCaT) were seeded in wells of 24-well plates containing complete culture medium (DMEM). After 24 h, the DMEM was replaced by serum-free DMEM, and cells were exposed to LPS of Escherichia coli (E. coli) (10 μg mL ) for 24, 48, and 72 h. The cells were subjected to specific parameters of phototherapy (PT) (LASERTable-InGaAsP-780 ± 3 nm, 25 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 46 publications
1
2
0
Order By: Relevance
“…37 However, the maintenance of intensified synthesis of inflammatory mediators in the tissue may reduce the proliferation and chemotaxis activities of oral mucosal cells. 38,39 In the present study, enhanced hIL-6 gene expression and IL-6 synthesis occurred when gingival fibroblasts and oral keratinocytes were seeded on Ti surfaces and exposed to TNFα (Figures 3 and 5). Downmodulation of hIL-6 gene expression and IL-6 synthesis occurred in those groups in which cells were seeded on EGF-coated Ti surfaces (Figures 3 and 5).…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…37 However, the maintenance of intensified synthesis of inflammatory mediators in the tissue may reduce the proliferation and chemotaxis activities of oral mucosal cells. 38,39 In the present study, enhanced hIL-6 gene expression and IL-6 synthesis occurred when gingival fibroblasts and oral keratinocytes were seeded on Ti surfaces and exposed to TNFα (Figures 3 and 5). Downmodulation of hIL-6 gene expression and IL-6 synthesis occurred in those groups in which cells were seeded on EGF-coated Ti surfaces (Figures 3 and 5).…”
Section: Discussionsupporting
confidence: 51%
“…This response is crucial to the induction of rapid recruitment of polymorphonuclear cells and the onset of the subsequent steps that characterize the wound‐healing process 37 . However, the maintenance of intensified synthesis of inflammatory mediators in the tissue may reduce the proliferation and chemotaxis activities of oral mucosal cells 38,39 . In the present study, enhanced h IL‐6 gene expression and IL‐6 synthesis occurred when gingival fibroblasts and oral keratinocytes were seeded on Ti surfaces and exposed to TNF‐α (Figures 3 and 5).…”
Section: Discussionmentioning
confidence: 54%
“…It is known that light of different wavelengths and intensities influences the activity of ion channels, increasing ion permeability into cells (Djavid, Bigdeli, Goliaei, Nikoofar, & Hamblin, 2017;Pansani et al, 2017;von Leden et al, 2013). In particular, the effect of NIR on brain tissue in vivo was studied: 808 nm light was found to activate NMDARs (Uozumi et al, 2010), protect cells from the destructive effect of high Ca 2+ concentration, promote the excretion of Ca 2+ from cells, and prevent excitotoxicity (Huang, Nagata, Tedford, & Hamblin, 2014).…”
mentioning
confidence: 99%
“…PBMT has emerged as a potential alternative to chemical agents (including antibiotics) for treating diseases with microbial and/or inflammatory origins (de Freitas and Hamblin 2016). With regard to periodontitis, studies have shown that GECs exposed to PBMT, when challenged with lipopolysaccharide (LPS) or heat-killed periodontal pathogens, enhance their viability and proliferation rate and alter the production of proinflammatory molecules (Pansani et al 2018). While the host cell response induced by a single type of PAMP has been widely studied (Maldonado et al 2016; Dickson and Lehmann 2019), this model does not address the cellular response to intact microbes, presenting multiple PAMPs and other molecules that might modulate the response.…”
Section: Discussionmentioning
confidence: 99%